2018
DOI: 10.1111/age.12720
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAnet: a comprehensive Sus scrofa lncRNA database

Abstract: Long noncoding RNAs (lncRNAs) constitute a large class of functional non-coding RNAs that play important roles in many biological processes. Thousands of lncRNAs have been identified in mammals. Pig is an important farm animal and biomedical model. It is essential to create a Sus scrofa lncRNA database to enable further study of the function and evolution of lncRNAs. In this study, we built a systematic S. scrofa lncRNA database named lncRNAnet that contains 53 468 S. scrofa lncRNAs with their sequence charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Therefore, understanding the underlying mechanisms of myogenesis is particularly important. Although thousands of lncRNAs have been identified [38,50], a minority of functional lncRNAs, such as TncRNA [51], lncMD [52], H19 [52][53][54][55][56], and lncIRS1 [57], are involved in mammal myogenesis. MEG3, a differentially expressed lncRNA during postnatal skeletal muscle development in pigs, has four crucial polymorphism sites associated with back fat thickness [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the underlying mechanisms of myogenesis is particularly important. Although thousands of lncRNAs have been identified [38,50], a minority of functional lncRNAs, such as TncRNA [51], lncMD [52], H19 [52][53][54][55][56], and lncIRS1 [57], are involved in mammal myogenesis. MEG3, a differentially expressed lncRNA during postnatal skeletal muscle development in pigs, has four crucial polymorphism sites associated with back fat thickness [39].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid adoption of RNA-seq technologies, thousands of lncRNA in the genome have been discovered in various species, their functions in various biological processes have been demonstrated (Geng et al, 2013; Gong et al, 2015b; Volders et al, 2015; Liang et al, 2018). However, compared with those of human and mouse, the lncRNA resources in pig are relatively limited (Quek et al, 2015; Liang et al, 2018). In this study, we identified a total of 8,166 novel lncRNAs, greatly expanding the genomic information of non-coding RNAs in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The porcine translational research database is a manually curated, genomics- and proteomics-based research resource ( 45 ). Lastly, LncRNAnet is a comprehensive Sus scrofa long non-coding RNA database ( 46 ).…”
Section: Resultsmentioning
confidence: 99%